2009
DOI: 10.1093/annonc/mdn749
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of cisplatin (C), gemcitabine (G) and gefitinib for advanced urothelial tract carcinoma: results of Cancer and Leukemia Group B (CALGB) 90102

Abstract: Background: This phase II trial (Cancer and Leukemia Group B 90102) sought to determine the efficacy of cisplatin, standard infusion of gemcitabine and gefitinib in patients with advanced urothelial carcinoma.Patients and methods: Eligible patients had previously untreated measurable disease, Eastern Cooperative Oncology Group (ECOG) performance status of zero to two and creatinine clearance >50 ml/min. Treatment consisted of cisplatin 70 mg/m 2 day 1 and gemcitabine 1000 mg/m 2 on days 1 and 8 given every 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 24 publications
3
49
0
3
Order By: Relevance
“…The ORR and median TTP in this trial were similar to those observed in other studies of GC and MVAC chemotherapy. 52 A phase 2 trial that evaluated trastuzumab in combination with paclitaxel, carboplatin, and gemcitabine was conducted in 109 patients with advanced HER-2 overexpressing TCC (defined by IHC or fluorescence in situ hybridization). The ORR was 70%, with 5 patients achieving a CR.…”
Section: Discussionmentioning
confidence: 99%
“…The ORR and median TTP in this trial were similar to those observed in other studies of GC and MVAC chemotherapy. 52 A phase 2 trial that evaluated trastuzumab in combination with paclitaxel, carboplatin, and gemcitabine was conducted in 109 patients with advanced HER-2 overexpressing TCC (defined by IHC or fluorescence in situ hybridization). The ORR was 70%, with 5 patients achieving a CR.…”
Section: Discussionmentioning
confidence: 99%
“…Again, however, preclinical activity has not translated into clinically relevant activity. A phase II study of GC plus the TKI gefitinib showed an ORR of 36% and MS of 11.1 months, but there was excessive toxicity (67). A similar study of GC plus the monoclonal antibody cetuximab is also under way.…”
Section: Egfr/her2 Inhibitionmentioning
confidence: 97%
“…The monotherapy arm had poor results with most patients progressing at the first evaluation, but the dual therapy arm showed an ORR of 25%, median PFS of 16.4 weeks, and median OS of 42 weeks, suggesting that cetuximab may improve the efficacy of paclitaxel in this patient population. Two earlier phase II studies with gefitinib, an EGFR TKI, in both the first-and second-line setting for patients with advanced UC did not yield any improvements in PFS or OS [Philips et al 2009;Petrylak et al 2010]. [Wulfing et al 2009].…”
Section: Epidermal Growth Factor Family Inhibitionmentioning
confidence: 99%